CFD ANALYSIS OF CENTRIFUGAL AIR COMPRESSOR - Kumar, Putta Vithal Naga; Bharathi, V. V. Prathibha (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 8 No 1 & 2 (2021): Journal of Advanced Research in Instrumentation and Control Engineering(ISSN: 2456-1398), 2021)
A single-stage industrial centrifugal compressor is designed to operate at low- to go against the flow. An analysis technique for impeller design, incorporating an aerodynamic constraint is defined that involves solving for a value known as "t" and a suction ratio. One dimension of the impeller is constructed with radial tips and the other dimension uses vanes to help with diffusing the flow. In this paper, the theoretical calculation is only in terms of efficiency, the original ones were measured where the geometry modelling and mesh development is performed in the Gambit Pre-processor. Computational dynamic two-dimensional study of flow in the flow passage and pressure units of an in an impeller; and its interaction with the volute are done in FLUENT. and then CFD results are compared to the theoretical results. How to cite this article: Kumar PVN, Bharathi VVP. CFD Analysis of Centrifugal Air Compressor. J Adv Res Instru Control Engg 2021; 8(1&2): 1-5.